Crystal Structure and Hirshfeld Surface Analysis of 1-(4-Chlorophenyl)-5-{4-[(2-methylphenyl)methoxy]phenyl}-1H-Pyrazole - Aydin, Abdullah; Akkurt, Mehmet; Turanli, Sumeyye; Banoglu, Erden; Ozcelik, Nefise (Aperta, 2021)
The aim of the study is to explore the crystal structure and performe Hirshfeld surface analysis of 1-(4-chlorophenyl)-5-{4-[(2-methylphenyl)methoxy]phenyl}-1H-pyrazole. In the title compound, C23H19ClN2O, the 4-chlorophenyl, 2-methylphenyl and benzene rings are oriented with dihedral angles of 71.22(10), 31.82(9) and 59.76(9)degrees, respectively, with respect to the pyrazole ring. Pairs of molecules are linked by intermolecular C-H center dot center dot center dot O hydrogen contacts with R-2(2)(8) ring motifs forming sheets lying parallel to (100). Furthermore C-H center dot center dot center dot pi interactions also contribute to stabilizing the molecular packing. A Hirshfeld surface analysis has been used to confirm and quantify the supramolecular interactions which indicate that the most important contributions for the crystal packing are from H center dot center dot center dot H (42.5%) and H center dot center dot center dot C/C center dot center dot center dot H (35%) and H center dot center dot center dot Cl/Cl center dot center dot center dot H (12%) interactions.